Immigration: Where and Who Does Make a Difference (GESTIÓN Y TENDENCIAS, 2023)
This study analyzes the settlement patterns of the migrant population in Chile using 2021 data from the National Institute of Statistics (INE), in a context of relatively high economic development that attracts migratory flows. Applying Chi-square statistical tests, the research demonstrates a significant dependence between immigrants' nationality and their region of residence, rejecting the hypothesis of a random distribution. It characterizes migrants' labor market insertion into specific economic sectors by macro-zone, observing, for example, a concentration of neighboring-country nationalities in the north linked to mining and services, and a greater presence of the Argentine population in the southern and far-southern zones. The findings conclude that migration responds to structural economic dynamics and support networks, providing relevant input for the design of public integration policies.
Keywords: migration in Chile; regional economics; statistical demography; labor market; geographic distribution